Pengaruh Brand Image Terhadap Loyalitas Pelanggan yang Dimediasi Kepuasan Pelanggan Pada Rumah Makan Titin Trenggalek - Deby Santyo Rusandy (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This study aims 1) To test and explain the effect of brand image on customer loyalty at TITIN Restaurant Trenggalek. 2) To test and explain the effect of brand image on customer satisfaction at TITIN Restaurant Trenggalek. 3) To test and explain the effect of customer satisfaction on customer loyalty at TITIN Restaurant Trenggalek and 4) To test and explain customer satisfaction mediation relationship between brand image with customer loyalty at TITIN Restaurant Trenggalek.Penelitian using eksplanasi research methods conducted through data collection in the field. The assumptions used in this study are the variables that can be measured by using the responses of respondents with questionnaires, TITIN Trenggalek Household consumer population, and samples of 100 respondents / consumers, data analysis using multiple linear regression statistic method, test sobel and hypothesis testing. Based on the results of research indicate that 1) Brand imagedapat improve customer loyalty at Restaurant TITIN Trenggalek.2) Brand imagedapat improve customer satisfaction at Restaurant TITIN Trenggalek. 3) customer satisfaction can increase customer loyalty at TITIN Restaurant Trenggalek and 4) Customer satisfaction mediate the relationship between brand image with customer loyalty at TITIN Restaurant Trenggalek.